Prophetic Morals and Their Implementation for Society 5.0 - Taufik Rahman; Muzaiyanah Muzaiyanah; Suryati Suryati (Program Studi Komunikasi dan Penyiaran Islam UIN Raden Fatah Palembang, 2023)
Prophetic character education is useful in emulating the morals and behavior of the Prophet with its four main characteristics, namely shiddiq, tabligh, amanah, and fathanah. A person who is always guided by the truth, masters communication skills, and is able to solve problems. In this era, technology is very influential in changing behavior or morals. Moral problems that occur in this era must be very concerned. The focus of the discussion in this article is how to implement prophetic morals in the era of society 5.0. Because in this era humans and technology are very closely related. However, it is possible for us to always emulate prophetic morals in everyday life. The research used in this article uses literature review by collecting data or literature that has an attachment to the theme to be discussed from journals, books and other writings which are used as reference material in the preparation of this article. The results of this study concluded that prophetic morals or prophetic morals are relevant and important to be applied in the midst of society 5.0 to form a civilized society without losing the existence of the progress of an era that must be followed and adopted.